2004
DOI: 10.1111/j.1365-2842.2004.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Edentulousness, denture wear and denture needs of Indian elderly – a community‐based study

Abstract: India has a large geriatric population (60+ years) of 77 millions, comprising 7.7% of its total population. One of the major handicaps in the elderly is loss of teeth, affecting their mastication, dietary intake and nutritional status. The present study was planned to assess the level of edentulousness, denture wearing and denture needs of the elderly in the community and to study the correlation between oral health parameters and socio-demographic variables, diet and body mass index (BMI). A total of 1240 (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
99
5
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 13 publications
19
99
5
2
Order By: Relevance
“…This could be a possible reason for female being partially edentulous as they cannot opt for needed treatment to save teeth. 2 Also similar result was found in the study done among the people aged above 65 years in Turkey which also shows low literacy level and female gender to be high-risk groups for tooth loss. 10 Further, it was also observed that more unemployed people were partially edentulous than employed.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…This could be a possible reason for female being partially edentulous as they cannot opt for needed treatment to save teeth. 2 Also similar result was found in the study done among the people aged above 65 years in Turkey which also shows low literacy level and female gender to be high-risk groups for tooth loss. 10 Further, it was also observed that more unemployed people were partially edentulous than employed.…”
supporting
confidence: 76%
“…Women have better health seeking behaviors and more conscious for their appearance and this could be one of the main reasons that females are visiting dental clinic more frequently than male. 2 In the present study, Kennedy Class III is more frequent type followed by Class II, Class IV and Class I in the age group 25-50 years. In support to our findings, Shah et al have shown the similar result.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…8 In India, the unmet need to replace missing teeth in partially dentate patients was as high as 90% with a large number of elderly citizens having health and dental problems. 2 The unmet need for dental care was relatively high. Recent surveys conducted on the prosthetic status of Indonesian population revealed that only 4,6% people rehabilitate their missing tooth by using some type of prosthesis while others not wearing any.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The Indonesian Basic Health Research (RISKESDAS) 2007 showed that in age group of 35-44 years old, the average number of tooth loss or was indicated of extraction (M-T) was considered high which was 2.89 and reaching 3.35 in 2013. There was a tendency to incline percentage of people who had tooth loss along with the increasing age.…”
Section: Introductionmentioning
confidence: 99%